Hydrocarbon Pneumonitis After Repeated Exposure and Gasoline Aspiration with Differential Diagnosis Lung Tuberculosis - Setiadi, Satya; Rakhma, Sastia; Chozin, Iin Noor; Astuti, Tri Wahyu; Sugiri, Yani Jane R.; Yudhanto, Hendy Setyo; Erawati, Dini Rachma (Universitaas Brawijaya, 2025)
Introduction: Chemical pneumonitis is an uncommon condition. Hydrocarbon pneumonitis is a kind of chemical pneumonitis. The features of this disease are atypical and may manifest either abruptly or persistently. Lung tuberculosis is an endemic illness in Indonesia, with an estimated 969,000 patients exhibiting diverse characteristics that may resemble chemical pneumonitis. Case Report: A 29-year-old gas station attendant with a history of recurrent exposure to gasoline vapours and episodes of asphyxiation while syphoning gasoline. A thoracic CT scan with contrast reveals several bilateral nodules with a tree-in-bud pattern, suggestive of pulmonary tuberculosis, with chemical pneumonitis as a differential diagnosis. Utilising clinical data, including occupational history, body plethysmography and spirometry results (moderate restrictive), laboratory findings, CT scan pictures, and Volatile Organic Compound analysis (elevated hydrocarbon levels), the patient is diagnosed with hydrocarbon pneumonitis. Discussion: The differential diagnosis was excluded through the analysis of sputum using molecular rapid test, IGRA test, LJ culture, and AFB of bronchial washing fluid. The administration of inhaled corticosteroids is a viable therapeutic option for this situation. Following six months of medication and exposure avoidance, the patient's condition has been improving. The patient was initially diagnosed with suspected lung tuberculosis based on a thoracic CT scan with contrast revealing bilateral multiple nodules exhibiting a tree-in-bud pattern. However, considering the patient's occupational history involving exposure to gasoline vapour and a history of choking on gasoline, the radiological findings ultimately confirmed a diagnosis of hydrocarbon pneumonitis. Case management may be determined by the severity level; however, due to its rarity, no primary treatment option exists. Conclusion: Hydrocarbon pneumonitis is infrequently encountered in comparison to pulmonary tuberculosis. Inhaled corticosteroids are a treatment alternative that yields clinical improvement. This example illustrates those rare diseases, such as hydrocarbon pneumonitis, can mimic pulmonary tuberculosis.